Influence of Hexavanadates on Na+/K+- ATPase activity - Zdravković, Aleksandra N; Krstić, Danijela (Medicinski podmladak, 2016)
Introduction: There is a great interest in use of polioximetalates in clinical medicine, primary as an antibacterial, antiviral and antitumoral agents. Considering the key role of Na+/K+- ATPase in normal functioning of most animal cells as well as pivotal roles in cancer cell migration, the aim of this work was to examine the influence of new synthesized hexavandates [V6-CH3][Na]2, [V6-NO2][TBA]2, [V6-C3][H]2, [V6-C5d][TBA]2 on Na+/K+- ATPase activity. Materials and methods: The enzymatic activity of porcine cerebral cortex Na+/K+- ATPase was followed in the absence and presence of increasing concentration of [V6-CH3][Na]2, [V6-NO2][TBA]2, [V6-C3][H]2, [V6-C5d][TBA]2 (within the range 10-8 - 10-3 mol/L). The released Pi liberated from the enzymatic hydrolysis of ATP was determined by spectrophotometric method, using Perkin Elmer Lambda 35 UV-VIS spectrophotometer. Results: Investigated compounds inhibit the activity of Na+/K+ ATPase in dose-dependent manner within the investigated range. Obtained results indicate that all investigated compounds inhibit the Na+/K+ ATPase activity, but with different inhibiting power. [V6-NO2][TBA]2 (IC50 = 1,87 × 10-5 mol/L) was the most potent inhibitor of Na+/K+ ATPase, while [V6-C5d][TBA]2 showed the least potent inhibiting power (IC50 = 1,31 × 10-4mol/L) . The results are consistent with previously published a concentration-dependent inhibitory effect of polyoxometalates (inclunding polioxovandates) on ATPase activity from different model syistems. Conculusion: Based on the results, we can conclude that the examined compounds inhibit Na+/K+- ATPase activity in a dose-dependent manner. Inhibiting power of tested hexavanadates are different, and weaker than inhibiting power of decavanadates (tested earlier) on Na+/K+- ATPase activity, which is probably due to differences in charge, size and shape of these polioxometalates. Considering the role of this enzymes in the functioning of healthy cells and the development of the pathological conditions, it is possible that the inhibition of these enzymes with polyoxometallates contributions ( both in vitro and in vivo confirmed ) an anti-tumor , anti-viral and anti-bacterial properties of polyoxometallates. Key words: Na+/K+- ATPase, polyoxometalates, inhibition, hexavanadate (V6).